2019
DOI: 10.15294/biosaintifika.v11i2.18730
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Brown Sugar as a Nectar Substitute for Trichoglossus haematodus in Captivity

Abstract: Trichoglossus haematodus (Linnaeus, 1771) is nectarivorous bird that feed on nectar as a source of carbohydrate. In captivity, it is not practical to provide a continued diet of nectar from the flowers. Therefore, this study aimed to find other carbohydrate sources such as brown sugar as substitute nectar for T. haematodus. Twelve wild T. haematodus in four cages offered five types different brown sugar solution with different concentrations. Since brown sugar has low protein content, therefore the birds also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Yin et al (2017) stated that the lysine level in the diet will adjust feed intake, it can modify the secretion of satiety hormones (leptin and cholecystokinin). According to Namroud et al (2008), amino acid metabolite levels have been reported to serve as signals to regulate feed intake through an appetite-controlling mechanism., In this study showed that the lorikeets were fed palm sugar solution diet still look healthy and have shined, brightly coloured and smooth plumage the same as reported by Prijono and Rachmatika (2019). It seems that the amino acids content in the palm sugar solution diets were able to meet the amino acid requirement by the birds, especially lysin in siwalan sugar.…”
Section: Amino Acid Compositionsupporting
confidence: 79%
See 4 more Smart Citations
“…Yin et al (2017) stated that the lysine level in the diet will adjust feed intake, it can modify the secretion of satiety hormones (leptin and cholecystokinin). According to Namroud et al (2008), amino acid metabolite levels have been reported to serve as signals to regulate feed intake through an appetite-controlling mechanism., In this study showed that the lorikeets were fed palm sugar solution diet still look healthy and have shined, brightly coloured and smooth plumage the same as reported by Prijono and Rachmatika (2019). It seems that the amino acids content in the palm sugar solution diets were able to meet the amino acid requirement by the birds, especially lysin in siwalan sugar.…”
Section: Amino Acid Compositionsupporting
confidence: 79%
“…Furthermore, this study found that if three grams baby biscuits added to the palm sugar solution diets, the feed intake of nipah sugar was significantly higher (51.78±10.00 g) than the siwalan (41.75±10.26 g), and the other palm sugars (Table 2.). According to Prijono and Rachmatika (2019), siwalan sugar solution diet added with baby biscuit have higher energy content than siwalan sugar solution diet without baby biscuit. Therefore the birds were fed diets with high energy content, reduce the amount of feed intake.…”
Section: Sweetnesss Level (Sweetness Index and Degree Brix)mentioning
confidence: 99%
See 3 more Smart Citations